Leveraging the Power of Peer Groups for Refugee Integration - Maximilian Förster; Julia Klier; Mathias Klier; Katharina Schäfer-Siebert; Irina Sigler (Business & Information Systems Engineering, 2021)
Refugee integration, one long-term solution to the large number of people fleeing their home countries, constitutes a challenge for both refugees and host societies. ICT and especially online peer groups seem promising to support this process. Building on literature demonstrating the societal benefits of peer groups, this paper proposes a novel peer-group-based approach to address refugee integration and introduces both an online and offline realization. A randomized field experiment in cooperation with public (refugee) services and a non-governmental organization makes it possible to expand existing research by quantitatively demonstrating societal benefits of online peer groups and ICT for refugee integration. Further, this paper is the first to assess the effectiveness of online and offline peer groups in one experimental setup comparatively. Results show that peer groups provide substantial value with respect to the integration domains social bridges, social bonds, rights and citizenship as well as safety and stability. While the outcome of the various integration domains differs for online and offline peer groups, participants' adoption rates were higher for online peer groups.
Keywords: 000; Online peer group; Refugee integration; Field experiment; Design science